Integration of SRHR Education in Islamic Boarding Schools: a Study of Islamic Feminism - Masthuriyah Sa'dan (Yayasan Jurnal Perempuan, 2015)
Some of the Yellow Book (traditional source of Islamic Study) are taught in a traditional boarding school including sexual and reproductive health issues. Such discussion is the realm of the study of jurisprudence. However discussions in the Yellow Book are often gender-bias and less relevant to the women of today who have different sexual and reproductive health problems compared to their grandparents. As a result, many cases of sexual violence and women’s reproductive affecting female students because of lack of knowledge not to say being ”blind” of sexual and reproductive health and rights (SRHR). By using the approach of Islamic epistemology and feminist theological analysis, this paper will attempt to reconstruct the Islamic sciences by integrating the Islamic jurisprudence (fiqh) into the study of gender and social science.